Knowledge regarding obstetric danger signs among pregnant women - Ghimire, Bijaya; Pathak, Pratima; Ghimire, Pratima (Nepal Medical College Journal, 2022)
Knowledge of obstetric danger signs is crucial to reduce maternal morbidity and mortality by identifying the problems earlier and avoiding the delay in seeking obstetric care. According to World Health Organization (WHO) more than 70% of maternal deaths occur due to obstetric complications and most of these deaths occur in developing countries. Most of these are preventable if pregnant women can identify these life-threatening danger signs on time and seek appropriate emergency obstetric care. This study was conducted to assess the knowledge of obstetric danger signs among pregnant women. A descriptive cross-sectional study was carried out from 15th July to 30th August 2021, 194 pregnant women who visited the Gynaecology Outpatient Department in Nepal Medical College Teaching Hospital, were enrolled for the study. Data were collected through face to face interviews using a structured questionnaire. The study findings revealed that overall knowledge on obstetric danger signs was suboptimal (3.1%). The median knowledge score of respondents on antenatal danger signs was 30.0% (Q1-Q3=17.5-40), intra-natal danger signs was 0.0% (Q1-Q3=0-20) and postnatal danger signs were 25% (Q1-Q3=0- 25). Severe vaginal bleeding was the most frequently mentioned danger sign in each of the three gestational periods (antenatal: 78.9%, intra-natal; 29.9% and postnatal; 39.7%). In conclusion, service providers and health management teams should emphasize on information, education and communication for every pregnant woman focusing on obstetric danger signs to have better awareness and thereby reduce adverse maternal and neonatal outcomes.